From intermediary relationship to multiple relationships – option of developing the network position in the internationalisation process. An exploratory study of a Polish food company - Małys, Łukasz; Fonfara, Krzysztof (Olsztyn Economic Journal, 2019)
Traditionally, the internationalisation process of a company has been analysed from the perspective of entering foreign markets. Currently, it is often analysed within the so-called network models, which take into account the importance of business relationships. The process of entry is not understood as a process of entering a foreign market, but a process of entering a network of business relationships on a foreign market. Insidership in such networks is necessary for successful internationalisation. Being an insider in the network means having a certain network position. The aim of the paper is to identify based on a pilot study the possible way of building network position on foreign markets by Polish food companies. The paper will present a picture of one company, focusing on its operations on German market since the entry in 2006. The researched company started building network position on foreign markets by developing a strong relationship with one actor, who acted as key intermediary with the market. As a result of major change in the business environment, the company decided to revise the strategy and develop a number of weaker links with various actors. The paper presents a number of questions which raise from a pilot study and require further investigation.